Putative storage root specific promoters from cassava and yam : Cloning and evaluation in transgenic carrots as a model system - Arango Mejía, J.; Salazar, B.; Welsch, R; Sarmiento Salazar, F; Beyer, Peter; Al-Babili, S. (Springer, 2010)
A prerequisite for biotechnological improvements of storage roots is the availability of tissue-specific promoters enabling high expression of transgenes. In this work, we cloned two genomic fragments, pMe1 and pDJ3S, controlling the expression of a gene with unknown function from cassava (Manihot esculenta) and of the storage protein dioscorin 3 small subunit gene from yam (Dioscorea japonica), respectively. Using ?-glucuronidase as a reporter, the activities of pMe1 and pDJ3S were evaluated in independent transgenic carrot lines and compared to the constitutive CaMV35S and the previously described cassava p15 promoters. Activities of pMe1 and pDJ3S in storage roots were assessed using quantitative GUS assays that showed pDJ3S as the most active one. To determine organ specificities, uidA transcript levels in leaves, stems and roots were measured by real-time RT-PCR analyses showing highest storage root specificity for pDJ3S. Root cross sections revealed that pMe1 was highly active in secondary xylem. In contrast, pDJ3S was active in all root tissues except for the central xylem. The expression patterns caused by the cassava p15 promoter in carrot storage roots were consistent with its previously described activities for the original storage organ. Our data demonstrate that the pDJ3S and, to a lesser extent, the pMe1 regulatory sequences represent feasible candidates to drive high and preferential expression of genes in carrot storage roots.